The Effect of Multi Channel Retailing, Cooperation Synergity and Accounting Information Systems on Business Development Strategies that Impact on Business Performance - Royan, Franciscus Musa; Sawitri, Dyah; Riyadi, Slamet (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
In this study the researchers chose the research object, namely a building material trading company in Sampit, Central Kalimantan named PT. Samudra Mas Group. The urgency of this study is to determine whether the multi-channel retailing variable, cooperation synergy and accounting information systems affect business development strategies and ultimately have an impact on company performance. This is to ensure the use of a business development strategy for the next 5 years. The study was conducted using respondents who are employees of PT. Samudra Mas Group, which has director positions to middle management and has the authority to make decisions in company operations. Respondents amounted to 70 people. This research measurement method using Smart PLS Professional 3.0. Pulling data by observation, interviews and distributing questionnaires. The results showed that multi-channel retailing, synergy of cooperation and accounting information systems significantly influence business development strategies. As well as a business development strategy to mediate multi-channel retailing that affects business performance.